Dissociation of Immune Responses from Pathogen Colonization Supports Pattern Recognition in C. elegans - Twumasi-Boateng, Kwame; Shapira, Michael (PLOS ONE, 2012)
Caenorhabditis elegans has been used for over a decade to characterize signaling cascades controlling innate immune responses. However, what initiates these responses in the worm has remained elusive. To gain a better understanding of the initiating events we delineated genome-wide immune responses to the bacterial pathogen Pseudomonas aeruginosa in worms heavily-colonized by the pathogen versus worms visibly not colonized. We found that infection responses in both groups were identical, suggesting that immune responses were not correlated with colonization and its associated damage. Quantitative RT-PCR measurements further showed that pathogen secreted factors were not able to induce an immune response, but exposure to a non-pathogenic Pseudomonas species was. These findings raise the possibility that the C.elegans immune response is initiated by recognition of microbe-associated molecular patterns. In the absence of orthologs of known pattern recognition receptors, C. elegans may rely on novel mechanisms, thus holding the potential to advance our understanding of evolutionarily conserved strategies for pathogen recognition.